Uwarunkowania przyrodnicze rozwoju zrównoważonego Podola Centralnego (na przykładzie mikroregionu chmelnickiego) = Natural conditions for sustainable development of the Central Podillya (on the example of Khmelnytsky microregion) - Melnyk, Anatolij; Kostiw, Ludmyla (Journal of Education, Health and Sport, 2015)
Melnyk Anatolij, Kostiw Ludmyla. Uwarunkowania przyrodnicze rozwoju zrównoważonego Podola Centralnego (na przykładzie mikroregionu chmelnickiego) = Natural conditions for sustainable development of the Central Podillya (on the example of Khmelnytsky microregion). Journal of Education, Health and Sport. 2015;5(5):335-341. ISSN 2391-8306. DOI 10.5281/zenodo.17800 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A335-341 https://pbn.nauka.gov.pl/works/561059 http://dx.doi.org/10.5281/zenodo.17800 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 20.05.2015. UWARUNKOWANIA PRZYRODNICZE ROZWOJU ZRÓWNOWAŻONEGO PODOLA CENTRALNEGO (NA PRZYKŁADZIE MIKROREGIONU CHMELNICKIEGO) Natural conditions for sustainable development of the Central Podillya (on the example of Khmelnytsky microregion) Anatolij Melnyk Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Instytut Geografii Ludmyla Kostiw Lwowski Uniwersytet Narodowy im. Iwana Franki, Wydział Geografii Streszczenie Opracowanie zawiera ogólną charakterystykę czynników kształtowania struktury krajobrazu – budowy geologicznej, rzeżby, klimatu, wód powierzchniowych, roślinności i pokrywy glebowej typowego dla Podola Centralnego mikroregionu Chmelnickiego. Zbadana struktura krajobrazu na poziomie typów terenów. Analizą objęta struktura uzytkowania ziemi, obszary chronione oraz sieć ekologiczna. Biorąc pod uwagę wlaściwości typów terenów oraz charakter ich zagospodarowania okresliono glówne kierunki rozwoju zrównoważonego Podola Centralnego. One nawiązują się do zmiany struktury użytkowania ziemi oraz rozwoju sieci ekologicznej z uwzględnieniem istniejących obszarów chronionych. Słowa kluczowe: środowisko przyrodnicze, sieć ekologiczna, rozwój zrównoważony. Abstract The article describes natural components of the environment, such as geological structure, topography, climate, surface waters, flora, fauna and soil, in the area of Khmelnytsky microregion. This region is a dominant part of Central Podillya. The article is focused on the structure of geosystems. It is also analyzed here the state of land use in general, and due to the types of geosystems. Based on the properties of geosystems in the area of research it is developed here the recommendations for sustainable development of Central Podillya. These recommendations involve: changes in the structure of land use and development of the ecological network, taking into account existing and future protected areas. Keywords: environment, geosystem, ecological networks, sustainable development.